Morphological and crystallographic controls in the replacement of calcite and aragonite by cerussite and otavite. (15th January 2023) - Kim, YoungJae; Tekawade, Aniket; Lee, Sang Soo; Fenter, Paul
Abstract: Mineral replacement reactions are essential solid–fluid interactions in natural and industrial processes including metasomatism, diagenesis, and metamorphism, and sequestration of metal toxins from polluted water. Here, we explore the morphological evolution of aragonite and calcite (polymorphs of CaCO3 ) during their replacement by cerussite (PbCO3, an isomorph of aragonite) and otavite (CdCO3, an isomorph of calcite) in acidic aqueous solutions (with initial pH 3 to 4). Observations using scanning electron and synchrotron-based transmission X-ray microscopies reveal the formation of pseudomorphic shells (∼5–10 µm thick) of cerussite and otavite when Pb 2+ is reacted with either calcite or aragonite and when Cd 2+ is reacted with aragonite. The formation of pore space at the substrate-precipitate interface and within the precipitate is found to be key in promoting chemical exchange between the dissolving phase and the solution. In contrast, minimal reactivity is observed when Cd 2+ is reacted with calcite. These results demonstrate that the lack of substrate-precipitate epitaxy (either because of inconsistent symmetries or due to large lattice constant mismatch) is a critical factor that enables replacement of primary CaCO3 minerals by Pb- or Cd-bearing secondary minerals while epitaxial relationships can inhibit those reactions. When calcite and aragonite coexist, the replacement of aragonite by cerussite and otavite occurs preferentially over that of calcite. We postulate that the relative reactivity of calcite and aragonite to Pb 2+ and Cd 2+ can be determined by interplay between morphological and crystallographic properties of CaCO3 materials as well as solution chemistry. Our results reveal how coupled dissolution-precipitation processes of carbonate minerals can control mobility and bioavailability of lead and cadmium in environments where acidic metal-contaminated water interacts with carbonate-rich rocks and soils.